Design and Application of a 4 000 m Work-class ROV System for Deep-sea Scientific Exploration - TU Shaoping; ZHU Yinggu; XIANG Liyang; ZHANG Zhonghua; GUO Tianxiang (Kongzhi Yu Xinxi Jishu)
Targeting deep-sea ecological unmanned scientific research in operation waters exceeding 4 000 meters with operating power of 150 HP@50 Hz, the capability to carry diverse scientific research tools, and remote control functionalities, this paper proposes a design solution for a complete scientific work-class ROV system. The system employs design techniques of lightweight, high power-density ROV body, self-discharging double redundancy drive under Sea State 5 for cable deployment and recovery, conveniently-distributed and compact surface remote power supply controls, and combined operation tools. These innovations allow for 4 000 meter ROV flight, safe deployment, retrieval, and unmanned deep-sea scientific tasks, with some components even extendable to utilization in a 6 000 meter platform. Eventually, the engineering product version of the complete ROV system was engineered by incorporating key self-made components such as hydraulic compensation propellers, control light boxes, tool valve boxes, and underwater electronic pods. The system is subject to component-level, subsystem-level, and complete system-level tests, coupled with the first sea trial, and a rigorous nine-day, eight-dive deep-sea ecological research mission, gathering abundant scientific samples and data, thereby effectively validating the operation capability and reliability of this complete ROV system.